Цифрлық қоғамдағы ақпараттық жауапкершіліктің мәні мен табиғатын түсінуге теориялық және құқықтық тәсілдер - Isakhankyzy, А.; Alibayeva , G.A. (Bulletin of the Karaganda University “Law Series”, 2025)
The relevance of the research topic is determined by the lack of comprehensive research on the responsibili ties of subjects of information legal relations. The emphasis is on rights and interests, while the problem of responsibilities has not been adequately reflected in the scientific literature. The expansion of the spheres of information exchange determines the diversity of the interaction of various subjects, whereas these subjects have rights and, accordingly, are obliged to have legal duties. Legislation often regulates information obliga tions at the level of by-laws, which raises certain questions of both practical and theoretical nature. It should be noted that there are no exhaustive answers to the existing questions, as evidenced by the theoretical or practical significance of the topic. During the study, a significant amount of scientific literature and legisla tion of the Republic of Kazakhstan and foreign countries was studied. A comparative analysis of the current legislation has made it possible to identify common and distinctive trends in the development of approaches to the content and policy of information law, to identify prospects and problems. As a result of the research, specific conclusions are drawn about the state of scientific thought on information responsibilities, the need to intensify research on this issue in the light of the development of the information society and the actualization of threats and risks associated with information trafficking. The concept of information responsibilities and the general outlines of their classification are given. It is demonstrated that information responsibilities are subject to in-depth scientific analysis as a certain legal category that ensures the realization of information in terests.